Violence Against Women and Children, Vol 1: Mapping the Terrain. 2011
DOI: 10.1037/12307-001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of child victimization, abuse, crime, and violence exposure.

Abstract: Although the literature about the scope and nature ofthe problem ofchild victimization, abuse, crime, and violence exposure is large and growing, it is still far from satisfying the needs of policymakers, practitioners, and researchers. In this chapter, I examine and document the prevalence of the problem. DEFINITIONAL MATIERSThe epidemiology of child victimization, abuse, crime, and violence exposure is muddled by terminology, making an accurate counting of the problem harder. For example, take three ofthe ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
43
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 25 publications
3
43
0
1
Order By: Relevance
“…patients were two to three times higher than among men in population-based samples (e.g., between 8% and 13%; Finkelhor, 2011). It should also be noted that, generally, men may be more hesitant than women to reveal a history of sexual abuse, thus, the actual prevalence rate of childhood sexual abuse may be even higher than found in the present study.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…patients were two to three times higher than among men in population-based samples (e.g., between 8% and 13%; Finkelhor, 2011). It should also be noted that, generally, men may be more hesitant than women to reveal a history of sexual abuse, thus, the actual prevalence rate of childhood sexual abuse may be even higher than found in the present study.…”
Section: Discussionmentioning
confidence: 66%
“…Overall, it was found that the prevalence rates of childhood victimization were high among forensic psychiatric patients compared to prevalence rates in general populations (Finkelhor, 2011). While higher rates of childhood sexual abuse were observed among female compared to male forensic psychiatric patients, no significant gender differences were found with regard to the prevalence of emotional abuse, physical abuse, and physical neglect during childhood.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations